IMPLEMENTASI VALUE KARAKTER PADA MATA KULIAH ILMU LUGHAH DI PROGRAM STUDI DIRASAT ISLAMIYAH UIN SYARIF HIDAYATULLAH JAKARTA - LINTANG, DAUD (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2024)
This study aims to measure the application of character education values to students in the Lughah Science subject. His graduation achievement is not only to be able to master Arabic in terms of linguistics and linguistic segmentation, but the most important thing is the application of noble moral values in the teaching process of Lughah Subject, its implementation in all sectors of life to become the hope and manifestation of the main mission of an education. This research method is a qualitative method with data collection techniques using observation and interviews with students. The results of this study show that Dirasat Islamiyah students have been able to integrate the character values of Lughah Science in everyday life, it can be seen the impact on: a). The lecture process that uses the Qur'anic language with gentleness and accuracy of language, b). Students who are able to insert content of humanist character values in every lecture process, and c). Language manners that are able to be more touching and invite more artistic communication in the classroom and campus environment.